On human nature in early Judaism: creation, composition, and condition - García, Jeffrey P. (Journal of ancient Judaism, 2020)
This book is an analysis of early Jewish thought on human nature, specifically, the complex of characteristics that are understood to be universally innate, and/or God-given, to collective humanity and the manner which they depict human existence in relationship, or lack thereof, to God. Jewish discourse in the Greco-Roman period (4th c. BCE until 1st c. CE) on human nature was not exclusively particularistic, although the immediate concern was often communal-specific. Evidence shows that many of these discussions were also an attempt to grasp a general, or universal, human nature. The focus of this work has been narrowed to three categories that encapsulate the most prevalent themes in Second Temple Jewish texts, namely, creation, composition, and condition.